MENINGKATKAN KEMAMPUAN AGAMA DAN MORAL ANAK MELALUI PEMBIASAAN - Rohaniyah, Eka Setiawati, Hadi Sutiawan (Jurnal Pendidikan dan Penelitian Semesta Mendidik, 2024)
Religious moral ability is the ability of children to obey the rules/religious values held by the local community, namely human behavior that is in accordance with the expectations, rules, and habits of a certain group of people. Religious morality is important to develop because it will be the basis or foundation for children to navigate life. From the results of observations in the field of children aged 5-6 years old, the play group at KB Bina Umat found that children's abilities in the aspect of religious moral development were relatively low. The research technique used is Classroom Action Research which is carried out with the aim of improving the moral and religious abilities of children aged 5-6 years at KB Bina Umat. The data source of this study is 5-6 years old children in the play group, researchers, collaborators, and principals at KB Bina Umat.The results of the study show that learning through habituation can improve the religious moral ability of children aged 5-6 years at KB Bina Umat, Serang Regency. The success rate of the activity is significant. In pre-cycle activities, the average percentage of 38.67% increased to 55.67% in the first cycle, and increased to 90.33% in the second cycle.